EXPLORATION OF THE TRANSFORMATION OF GLOBAL STRATEGIC INDUSTRY TRADE NETWORKS: AN APPROACH TO UNDERSTANDING STRUCTURAL CHANGE AND ITS DETERMINING FACTORS - Ijang Faisal; Wawan Ichwanudin; Zaenal Aripin (PT. Kreatif Indonesia Satu, 2024)
Global trade has undergone significant transformation in recent decades, influenced by developments in information and communications technology (ICT), international trade policies, and shifts in global consumer preferences. Through this approach, research aims to understand how these factors interact with each other and shape the structure of global trade. Analysis shows that ICT developments have influenced global industrial structures by reshaping supply chains and facilitating the growth of e-commerce. On the other hand, international trade policies play an important role in shaping trade patterns and the geographic distribution of production, while shifts in global consumer preferences have changed the way companies operate and influenced their business strategies. By understanding the interactions between these factors, we can develop effective business strategies and government policies in managing structural changes in global trade networks to achieve sustainable and inclusive economic growth.